Maktabgacha yoshdagi bolalarni asosiy gimnastika vositalari orqali koordinatsion rivojlantirish - Toylibaev, S.M; Allambergenova, R.D (SCIENCE and SOCIETY, 2023)
The article talks about the development of motor skills in preschool children by means of basic gymnas- tics. Also, attention is paid to the structure and basic training of preschool children's motor activity for sports by means of basic gymnastics of a coordinating and developing orientation.
Keywords: preschool children; facilities basic gymnastics; coordination development; degree of physical development; age stages